2006
DOI: 10.1038/nm1424
|View full text |Cite|
|
Sign up to set email alerts
|

The autoimmune regulator (Aire) controls iNKT cell development and maturation

Abstract: The mechanism underlying the autoimmune polyglandular syndrome type-1 (APS1) has been attributed to defective T-cell negative selection resulting from reduced expression and presentation of autoantigens in thymic medullary epithelial cells (MECs). It has also been postulated that Aire is involved in development of regulatory T cells, although supporting evidence is lacking. Here we show that expression of Aire in MECs is required for development of iNKT cells, suggesting a role for iNKT cells in APS1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Clearly, the potential for Aire to impact on regulatory T-cell subsets provides a credible explanation of the disease profile of Aire-deficient individuals and evidence that the development of Treg is largely unaffected only highlights the need to examine NKT cells in Aire-deficient mice [18]. Speculation of a defect within the NKT cell compartment led to a recent study that reported a severe NKT cell deficiency in Aire-deficient mice [30]; however, the article was later retracted [31] and the issue remains unresolved. We have directly addressed the question by characterizing the size, composition and function of the thymic and peripheral NKT cell compartments of Aire-deficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the potential for Aire to impact on regulatory T-cell subsets provides a credible explanation of the disease profile of Aire-deficient individuals and evidence that the development of Treg is largely unaffected only highlights the need to examine NKT cells in Aire-deficient mice [18]. Speculation of a defect within the NKT cell compartment led to a recent study that reported a severe NKT cell deficiency in Aire-deficient mice [30]; however, the article was later retracted [31] and the issue remains unresolved. We have directly addressed the question by characterizing the size, composition and function of the thymic and peripheral NKT cell compartments of Aire-deficient mice.…”
Section: Introductionmentioning
confidence: 99%